Study of Qualitative Characteristics and Properties of Horse Meat - Abzhanova Sholpan; Rskeldiev Berdan; Kulazhanov Talgat; Baibolova Lyazzat; Uzakov Yasin (Journal of Pharmacy and Nutrition Sciences, 2019)
One of the main principles of state policy is to define the process of nutrition as a function of the relationship of a person with the environment. Nutrition should promote human adaptation to adverse environmental conditions. In this regard, the functions of nutrition are not only to meet the physiological needs of the body for nutrients and energy, but also to improve human health, prevent alimentary-related diseases associated with nutrition. The aim of the research was to develop the technology of meat products to create innovative technologies of functional products from meat for public catering.